Assessment of bird diversity, feeding guild and avitourism potential in Pulau Tinggi Marine Park, Mersing, Johor, Malaysia. - Mokhter, Normaisharah (2020)
Small islands are known for their fundamental role in providing vital pitstop for migratory birds. Moreover, island birds are important models for Island Biogeography Theory. However, research on birds on Malaysian islands are lacking whereas most research mainly concentrated on marine lives. Thus, a study was conducted in Pulau Tinggi Marine Park (2°18’N; 104°07’E) from March to August 2019 to fill this knowledge gap by fulfilling three objectives which are (i) to determine the bird diversity and relative abundance, (ii) to investigate the feeding guild of the birds in selected macrohabitat and (iii) to assess the potential of avitourism in Pulau Tinggi, Mersing, Johor. Three field methods were applied including mist-netting, direct observation, and camera trapping. Birding hotspots and important bird species according to the seven criteria of good nature tourism product were determined. At the same time, sets of questionnaires were distributed to the target informants to see the potential of having avitourism in Pulau Tinggi. A total of 43 bird species belonging to 24 families were recorded. Among these, 32 species were residents, four species were residents’ migrants and seven were migrants. In terms of conservation status, three species were listed as Near Threatened under International Union for Conservation of Nature (IUCN) Red List of Threatened Species. They were Grey-headed Fish Eagle (Haliaeetus ichthyaetus), Nicobar Pigeon (Caloenas nicobarica) and White-chested Babbler (Trichastoma rostratum). Nicobar Pigeon was found endemic to small forested islands. Bird diversity in Pulau Tinggi is also high with Shannon Weiner Index of 2.49. Result shows that coastal area is higher in bird richness with Margalef richness index value of H=2.25 compared to forest area with value of H=1.93. However, birds in the forest area were more evenly distributed with evenness index value of 0.58 over coastal with value of 0.38. Seven feeding guilds were successfully identified including carnivore, insectivore, frugivore, omnivore, carnivore-insectivore, frugivore-insectivore and granivore. The forest zone was mostly occupied by insectivore and frugivore while coastal zone was dominated by carnivore. Besides, there is also significant correlation between bill size and food size/diet preference (R=0.623, p=0.01). For avitourism prospect, six birding hotspots representing different macrohabitats were identified. Each macrohabitat supports different bird composition which highly influenced by different vegetation and food availability in the ecosystem. In addition, several birds were complied with the seven criteria of good nature tourism product. To conclude, documentation on bird diversity from this survey with birding hotspots recognision will become the baseline data for implementing avitourism in Pulau Tinggi. By accommodating high species richness and migratory species, beside the existance of an island endemic, these will be enough justification for protection and conservation of avian community in Pulau Tinggi. Above all, these components attract avitours with supplementary point on species that complied with good nature tourism product. Thus, Pulau Tinggi has a potential to be lifted as an avitourism site in the near future with a proper management plan.